A Campaign Without End? 'Dissident' Republican Violence in Northern Ireland. (April 2014) - Tonge, Jon
<x xml:space="preserve">Abstract</x> The greatest threat to stability in Northern Ireland comes from dissident republicans opposed to the peace process. But are these rejectionists a dying gasp or another phase of a centuries‐old struggle against British rule in Ireland? Jon Tonge investigates. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>